Analysis of the Influence of Freedom of Expression, Access to Information, and Political Participation on the Protection of Political Rights - Fauzan Fauzan; Arief Fahmi Lubis; Evy Febryani; Raihana Raihana (Westscience Press, 2024)
This research investigates the intricate interplay between freedom of expression, access to information, political participation, and the protection of political rights in Indonesia through a quantitative analysis. A sample of 1500 respondents from diverse demographics was surveyed, and the data were subjected to confirmatory factor analysis and structural equation modeling. The findings reveal strong positive relationships between freedom of expression, access to information, political participation, and the protection of political rights. The measurement model demonstrated robust psychometric properties, and discriminant validity was confirmed. While the model fit was acceptable, ongoing refinement is suggested. The R-Square value indicates that approximately 60.2% of the variance in the protection of political rights can be explained by the selected variables. The study contributes to the understanding of democratic governance in Indonesia, emphasizing the pivotal role of information, expression, and civic engagement in safeguarding political rights.